HUBUNGAN ANTARA KEGIATAN BERMAIN MAKE A MATCH DENGAN KEMAMPUAN BERHITUNG ANAK USIA DINI - Ai Siti Komariah ai; Yuyun Yulianingsih; Aam Kurnia (Generasi Emas: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
The purpose of this study was to determine the reality of making match play activities, the reality of early childhood numeracy skills, and the relationship between make a match play activities and early childhood numeracy skills in Group B2 RA Mukhlishiina Lahuddiin Cinunuk Village, Cileunyi District, Bandung Regency. The research method used in this study uses a quantitative correlational method. The results of the analysis on the activity of playing make a match obtained an average value of 80.95. This value is in the 80-100 interval with a very good category. Meanwhile, early childhood numeracy skills obtained an average value of 78.6. This value is in the 70-79 interval with a good category. The relationship between the activities of playing make a match with early childhood numeracy skills obtained a correlation coefficient of 0.937. The value of this correlation coefficient is included in the very strong category because it is in the 0.800-1,000 interval. The results of the significance test obtained tcount = 10.04 > ttable value = 2.14. This means that the null hypothesis is rejected and the alternative hypothesis is accepted. Thus, the activity of playing make a match has a significant relationship with early childhood numeracy skills in Group B2 RA Mukhlishiina Lahuddiin Cinunuk Village, Cileunyi District, Bandung Regency. Meanwhile, the contribution or influence on the activity of playing make a match on early childhood numeracy skills is 87.8%. Thus 12.2% is influenced by other factors.